Quantitative Analysis of Hexahydro-1, 3, 5-trinitro-1, 3, 5, Triazine/Pentaerythritol Tetranitrate (RDX–PETN) Mixtures by Terahertz Time Domain Spectroscopy. Issue 12 (December 2015) - Sleiman, Joyce Bou; Bousquet, Bruno; Palka, Norbert; Mounaix, Patrick
Absorption spectra of explosives such as hexahydro-1, 3, 5-trinitro-1, 3, 5-triazine (RDX), pentaerythritol tetranitrate (PETN), and mixtures of both were measured by terahertz time domain spectroscopy (THz-TDS). Chemometrics was applied to quantitative analysis of terahertz absorbance spectra obtained in transmission mode to predict the relative amounts of RDX and PETN in samples containing pure components or their mixtures. This analysis was challenging because significant spectral overlap prevented identification of each product fingerprint. Partial least squares (PLS) regression models were thus applied to the terahertz spectra. A comparison between the so-called PLS1 and PLS2 algorithms was performed to predict the PETN concentrations in mixture samples. PLS2 demonstrated better predictive ability than PLS1 with RM SE value lower than 3.5 mg for 400 mg total weight pellets. Moreover, the influence of the highly overlapping spectral frequency band was investigated by reducing the original 0.2–3 THz (6–100 cm −1 ) spectral band to 1.8–3 THz (60–100 cm −1 ). The predictive ability was quite similar in both cases, highlighting the excellent ability of chemometrics to perform quantitative analysis when applied to THz-TDS data, even in the case of highly overlapping spectra.